Efetividade do instrumento econômico de renúncia tributária e suas condicionantes para geração do benefício socioambiental - Maia, Carolina Bortolotte (2011)
Implementing various environmental management tools, in an integrated way, is fundamental for more effective results. Considering that Brazil adopts an environmental management system strongly centered on control and command instruments, the need for economical instruments to create a Public Policy for Environmental Protection becomes evident. This study intends to expand the possibilities that are available in Brazil's tax system, by using economical mechanisms – particularly Tax Concession, to advance the sustainable development and its effectiveness, due to the benefits generated to the corporation’s social-environmental activities.The method applied was the documental and bibliographical research to explore and understand the mechanisms of the Tax System and the Political and Legal boundaries, as well as the positive and negative aspects about the use of the economical instrument called Tax Concession, for the configuration of a Contemporary Environmental Public Policy, based on the Precaution Principle and on tax reduction.This study attempts to highlight that the Public Environmental Policy, besides control and command mechanisms, has Economical instruments as allies. In this matter, it was observed that Tax Concession can produce significant benefits to the environment, producing the desirable response from the business community.For this purpose, directions for developing an efficient contemporary environmental policy are being presented, and also a proposal for the minimum requirements for achieving tax benefits, by the Law project "Ecological Income Tax", with the final goal of reaching a sustainable development.